2013
DOI: 10.1155/2013/989508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mild and Severe Knee Joint Pain on Various Activities of Daily Living in the Female Elderly

Abstract: This study aimed to examine the differences in the ability to perform various activities of daily living (ADLs) among groups with various knee problems. The participants consisted of 328 elderly females (age 60–94; mean age 76.1 years; standard deviation 6.2). The subjects were classified into three groups: those without knee pain, those with mild knee pain, and those with severe knee pain. ADLs with markedly higher (>97%) and lower (<38%) achievement rates in the group without knee pain were not significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…1 In Japan, 54.6% of people aged 40 and older are reported to have radiographic knee OA, including many who are asymptomatic, and the prevalence increases with age. 2 Knee OA can lead to restrictions in ADLs, [3][4][5] declines in quality of life, 6 and subsequent detriments to mental health. 7,8 The relationship between depression and knee OA has been gaining attention recently, with some recent studies showing associations between knee OA and development of depressive symptoms, 9,10 but most of these studies focused on radiographic changes rather than actual symptoms in their assessments of knee OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In Japan, 54.6% of people aged 40 and older are reported to have radiographic knee OA, including many who are asymptomatic, and the prevalence increases with age. 2 Knee OA can lead to restrictions in ADLs, [3][4][5] declines in quality of life, 6 and subsequent detriments to mental health. 7,8 The relationship between depression and knee OA has been gaining attention recently, with some recent studies showing associations between knee OA and development of depressive symptoms, 9,10 but most of these studies focused on radiographic changes rather than actual symptoms in their assessments of knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…A validated self-administered questionnaire in Japanese based on an English version of the Western Ontario and McMaster Universities Osteoarthritis Index 18,19 was used to assess knee pain (5 items) and functional impairment (17 items) (Table S1). Each item was measured on a 5-point Likert scale (1)(2)(3)(4)(5). Pain was assessed separately in each knee, and the score for the knee with the higher level of pain was used as the representative value for each participant.…”
Section: Baseline Examinationsmentioning
confidence: 99%
“…Knee pain is a physical symptom common in older adults, and is a major contributor to functional limitation and disability . However, previous studies showing the impact of knee pain on gait speed decline in older persons are limited .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Knee pain is a physical symptom common in older adults, 9 and is a major contributor to functional limitation and disability. 10,11 However, previous studies showing the impact of knee pain on gait speed decline in older persons are limited. 12 For example, a crosssectional study reported that knee pain in middle-aged women, with or without knee osteoarthritis, showed an inverse correlation with gait speed.…”
Section: Introductionmentioning
confidence: 99%
“…They have difficulty in walking or standing up [5,6]. There are considerable individual differences in the degree of these conditions even among the elderly with knee joint pain.…”
Section: Introductionmentioning
confidence: 99%